Strategi Komunikasi Dakwah dalam Pesan lagu Cari Berkah Wali Band - Burhanudin Ata Gusman; Yazida Ichsan; Faradina Nur Setianingsih; Istiani Nur Kasanah (SALIHA: Jurnal Pendidikan & Agama Islam, 2022)
In today's era, most teenagers in Indonesia like western culture. And there are so many who take western culture as an example in their lives, which in their view is art. The lyrics of songs with Islamic nuances are currently popular and loved like all circles of society, both small children to adults. In this day and age, many da'i preach only in big events such as recitations, but very few preach in residential villages. From there, a new da'wah strategy emerged, namely through songs with Islamic nuances. One of the musicians who is committed to carrying out da'wah through his song lyrics is Waliband. This research is a library study which in searching for literature comes from various journals and other sources. And the method of analysis in this research uses qualitative methods by describing systematically and factually. Based on the results of this study, it is explained that the da'wah strategy through the message of the song lyrics of the search for blessings by Waliband describes a good moral message with the aim that we as humans help each other, help fellow humans in daily life which will later get rid. from Allah, so that his life is a blessing. Because we as servants of Allah SWT continue to preach, spread goodness to all Muslims in this world, preaching does not have to be in assemblies such as mosques, etc. but can be done with different strategies and methods, for example, da'wah with music, games and so on.